Evaluation of the E-Mental Health Mindfulness-Based and Skills-Based “CoPE It” Intervention to Reduce Psychological Distress in Times of COVID-19: Results of a Bicentre Longitudinal Study - Bäuerle, Alexander; Jahre, Lisa; Teufel, Martin; Jansen, Christoph; Musche, Venja; Schweda, Adam; Fink, Madeleine; Dinse, Hannah; Weismüller, Benjamin; Dörrie, Nora; Junne, Florian; Graf, Johanna; et al. (Frontiers in Psychiatry, 2021)
Background: The SARS-CoV-2 pandemic poses immense challenges for health care systems and population-wide mental health. The e-mental health intervention “CoPE It” has been developed to offer standardized and manualized support to overcome psychological distress caused by the pandemic. The aim of this study was to assess the effectiveness of “CoPE It” in terms of reducing distress (primary outcome), depression and anxiety symptoms, and improving self-efficacy, and mindfulness (secondary outcomes). Furthermore, the intervention's usability, feasibility, and participants' satisfaction with “CoPE It” was evaluated (tertiary outcome). The study protocol has been published previously. Methods: A bicentre longitudinal study was conducted from April 27th 2020 to May 3rd 2021. N = 110 participants were included in the analyses. The intervention consisted of four modules featuring different media promoting evidence-based methods of cognitive behavioral therapy and mindfulness-based stress reduction. Difference in psychological distress between baseline (T0) and post-intervention (T1) were analyzed by repeated measure analysis of covariance. Mixed linear models were applied to assess moderating effects. Depressive symptoms, generalized anxiety symptoms, self-efficacy, and mindfulness were compared between baseline (T0) and post-intervention (T1) via t-tests. Usability of the “CoPE It” intervention and participants' satisfaction was evaluated by calculation means and frequencies. Results:Primary outcome: A significant effect of time on psychological distress at post-intervention (T1) after controlling for age, gender, education, mental illness and attitudes toward online interventions was found. Depressive and anxiety symptoms, and mindfulness were a significant moderators of the relationship between time and psychological distress for consistent wording. Secondary outcomes: There was a significant decrease in depressive symptoms and generalized anxiety, and a significant increase in self-efficacy and mindfulness between baseline (T0) and post-intervention (T1). Tertiary outcomes: 95.83% of the participants thought the “CoPE It” intervention was easy to use and 87.50% were satisfied with the “CoPE It” intervention in an overall, general sense. Conclusion: The e-mental health “CoPE It” intervention seems to be an effective approach in reducing psychological distress, anxiety and depressive symptoms, and in enhancing self-efficacy and mindfulness during the COVID-19 pandemic. Participants' satisfaction and the program‘s feasibility, and usability were proven to be high. Clinical Trial Registration:www.ClinicalTrials.gov, identifier: DRKS00021301.